Literary Education in Czech Schools - Hník, Ondřej; Jindráček, Václav (Bohemistyka, 2023)
The authors of the paper introduce the readers to the context of the literary edu- cation in Czech schools. In Czech milieu were hold many polemic discussions, that are known at least since the year 1890. Into that discussions were involved big personalities of conterporary cultural live, among others Hubert Gordon Schauer, František Krejčí, Jaroslav Vlček, Otakar Hostinský, Vilém Mathesius and Jan Mukařovský. In many cases thay evaluated teaching of literature as distant from the life of a young generation, too historically oriented, and pointed out its deficient connection with aesthetics of a literary work. They held against excessive memorization as contrary to the little emphasis put on reading and analysis of literary work. The authors of the paper are strongly convinced that even after more than 130 years of polemic discussions about the form of literary education and a series of reforms (which cannot even be taken into account because it is not clear where one reform ends and another begins), the real curriculum of literary education has not fundamentally changed.